Factors affecting users' continuance intention of mobile social network service. Issue 13 (26th October 2019) - Yen, Wan-Chu; Lin, Hsin-Hui; Wang, Yi-Shun; Shih, Ying-Wei; Cheng, Kai-Hong
ABSTRACT: This study investigates the factors that influence users' intention to continue using social network service applications (apps) on mobile devices. We drew on the uses and gratifications (U&G) paradigm and innovation diffusion theory; these were augmented with the factors that characterize mobile social network service (MSNS) usage. The proposed framework explained the relationships between these factors and the intention to continue using MSNS apps. A web-based survey was used to collect data for analysis. The results indicated that critical mass, mobility, compatibility, purposive value, and entertainment value were important drivers of users' intention to continue using MSNS apps. The findings contribute to existing U&G paradigm, innovation diffusion theory, and MSNS usage literature. The paper closes with a discussion of useful insights relevant to researchers and practitioners in terms of developing and implementing MSNS apps that have high retention rates.